Susan's dilemma - Jaikumar, Saravana, (SAGE Knowledge. Cases., 2017)
Susan, a dog lover and an entrepreneur, wanted to start a franchise of Dog Shop in Ahmedabad. She had the data regarding the demand and costs incurred by Dog Shop on various verticals in its first year of operations. Based on this data and using an appropriate investment appraisal technique, Susan had to evaluate the three franchisee options offered by the company. The case can be used in any program and course which includes investment appraisal as part of its syllabus.